Importance of Desensitization for Autistic Children in Dental Practice - Eva Martínez Pérez; Alberto Adanero Velasco; Víctor Gómez Clemente; Mónica Miegimolle Herrero; Paloma Planells Del Pozo (MDPI AG, 2023)
Objectives: Dental treatment in special needs patients, including children with autism, can be accomplished by reducing the behaviors that can reduce fear, as it has been demonstrated in other studies. The present study aims to examine the influence of the latency time elapsing between desensitization and the real dental situation on facilitating the access of children with autism to dental treatment. Study design: Nineteen patients with autism, who were aged 3-14 years and attended the Special Education Center in Madrid but were living with their parents at home, were selected for the study. All children in the sample were subjected to a desensitization process before attending the real dental office. Two study groups were established: the latency period between the last desensitization and the real situation was one day for the first group and seven days for the second group. An experimental study was conducted to assess the child's cooperation in the dental chair; the dental examination was divided into several steps and the highest step reached by each child was recorded. Results: There is a statistical difference in the number of steps reached between the children who received the information just before the examination date and the children who experienced a longer latency period between receiving the information and experiencing the examination. Conclusions: We would like to emphasize the importance of providing information in advance when dealing with autistic children; this information should be as close as possible to the real situation. Additionally, we would like to stress the importance of inter-cooperation between parents, educators, and pediatric dentists in order to guarantee adequate oro-dental care for autistic children. Further studies with larger sample sizes and a control group are recommended.